Magnetic ionic liquids based on transition metal complexes with N-alkylimidazole ligands. (22nd November 2018) - Chand, Deepak; Farooq, Muhammad Qamar; Pathak, Arjun K.; Li, Jingzhe; Smith, Emily A.; Anderson, Jared L.
Abstract : Nickel(ii ), cobalt(ii ) and manganese(ii ) N -alkylimidazole bis[(trifluoromethyl)sulfonyl]imide magnetic ionic liquids were synthesized from their chloride intermediates and their physicochemical properties studied. Abstract : In this study, magnetic ionic liquids (MILs) consisting of Ni(ii ), Co(ii ), and Mn(ii ) and paired with the bis[(trifluoromethyl)sulfonyl]imide [NTf2 − ] anion were synthesized from their water soluble chloride intermediates. The MILs feature low viscosity, high hydrophobicity, and hydrolytic stability making them attractive candidates for a number of highly interdisciplinary applications.